Consequences of conversion of native Mesic grassland to coniferous forest on soil processes and ecosystem C and N storage - McKinley, Duncan Crannell (Kansas State University, 2006)
Juniperus virginiana, an important woody plant invader in the U.S. Central Plains, has increased considerably in density and cover in large areas previously dominated by tallgrass prairie. Change in the phenology and nitrogen use efficiency of the dominant plant communities as J. virginiana replaces native prairies may lead to increased plant productivity and biomass accumulation, but may also alter the microclimate and litter quality that affect soil microbial communities responsible for key soil processes. I have focused my investigations on changes in key soil processes that could lead to differences in soil N availability, as well as changes in ecosystem C and N pools and fluxes as J. virginiana expands into native grasslands. Juniperus virginiana forest soils exhibit greater cumulative annual net N mineralization (11.52 ± 0.38 µg N g¯1 soil y¯1) compared to prairie soils (7.90 ± 0.26 µg N g¯1 soil y¯1) (F = 60.67, P = 0.016), yet slightly reduced potential soil C flux. Examination of internal soil N cycling revealed that both J. virginiana and prairie soils minimize potential soil N losses, by rapid microbial immobilization of inorganic N, and constraining nitrification via substrate limitation or environmental constraints. Leaf-level photosynthetic nitrogen use efficiency (NUE) was over a magnitude higher in the dominant grass, Andropogon gerardii, but high annual ecosystem-level NUE and greater soil N availability may contribute to the higher productivity and rapid accrual of C in newly established J. virginiana forests. Increased plant productivity and elimination of fire in J. virginiana forests have allowed at least 80,000 kg ha-1 increase in ecosystem C storage in about half a century. Soil organic C, an important long-term sink, has also increased significantly in J. virginiana forests, with approximately 34% replacement of C4 grass-derived soil C with new C from trees in the A-horizon. The observed high productivity of J. virginiana and increased N availability necessary to support continued plant biomass accumulation are possible because of substantial (~ 44%) increase in ecosystem N in measured pools, which is a likely a result of reduced volatilization of N from biomass burning, possible increased exogenous N inputs, and/or N translocation from deeper soil horizons. Reduced fire return intervals in prairie provide an opportunity for J. virginiana to establish and facilitate N accrual, which may allow this species to accelerate is own establishment through creating conditions of increased N availability and efficient utilization of N.
Keywords: Juniperus; Invasion; Woody plant encroachment; Soil processes; Nitrogen cycling; Redcedar; Biology, Ecology (0329)